Dilemmas faced by pre-service teachers when learning about and implementing a game-centred approach. (May 2015) - Harvey, Stephen; Cushion, Christopher; Sammon, Paul
Game-centred approaches (GCAs) were designed for the effective integration of skills into contextualized situations. Despite a plethora of research, few studies explore the articulations between pre-service teachers' experiences, conceptual understanding, pedagogical practices, the wider cultural and political realities of teaching and their impact on the learner. This paper uses Windschitl's (2002) framework of practice dilemmas to structure an analysis of various dilemmas faced by a cohort of English pre-service teachers on a one-year Postgraduate Certificate in Education learning about and implementing a GCA. Nineteen (6 male; 13 female) postgraduate students based at a university in the East of England agreed to participate in the study. Data were generated through an online discussion board, case study log and from focus group interviews. Data analysis was an inductive iterative process that integrated the multiple data sources. The analysis was conducted through a constant comparison between the different sources to identify themes that were mapped against Windschitl's (2002) heuristic. Supported by the realization of their own participation in 'traditional' physical education programmes, this cohort of pre-service teachers attempted to integrate GCAs into their practice. Significant challenges included the pre-service teachers' own fragile conceptual understandings and pedagogical expertise in GCAs, exacerbated by current institutionalized practices within most physical education programmes.